The more you know, the better you drink: The new drinking culture in Italian wine production areas. (3rd July 2016) - Beccaria, Franca; Rolando, Sara
Abstract: Introduction : The paper complements an epidemiological analysis of secondary data that compared levels of consumption, alcohol-related mortality and morbidity in territories in Piedmont (N-W Italy), characterized by a different involvement with wine culture, and which showed lower alcohol-related risks in areas of production. Aims : The main aim is to shed light on these epidemiological results through qualitative methods, focusing on meanings attributed to drinking and on mechanisms of regulation that could explain why in wine-producing areas alcohol-related risks appear to be lower. Methods : Eighty-one in-depth individual interviews have been conducted. The sample consisted of males and females, from three cohorts (aged 18–25; 45–52; 70–77 years) and covering two areas (with higher versus lower vineyard acreage). Results : In areas characterized by wine production the traditional alcohol socialization process within the family is more persistent. In these areas, the traditional drinking culture has been not only valued, but also renewed, by emphasising the importance of proper drinking and the knowledge related to it. Conclusions : The alcohol socialisation process and the emphasis on wine as a cultural product seem to be the most relevant protective factors, contributing to the lower alcohol consumption and counteracting the widespread risk of alcohol consumption patterns.